Woodland caribou persistence and extirpation in relic populations on Lake Superior - Bergerud, Arthur T.; Dalton, W. J.; Butler, H.; Camps, L.; Ferguson, R. (Rangifer, 2007)
Extended: The hypothesis was proposed that woodland caribou (Rangifer tarandus caribou) in North America had declined due to wolf predation and over-hunting rather than from a shortage of winter lichens (Bergerud, 1974). In 1974, two study areas were selected for testing: for the lichen hypothesis, we selected the Slate Islands in Lake Superior (36 km2), a closed canopy forest without terrestrial lichens, wolves, bears, or moose; for the predation hypothesis, we selected the nearby Pukaskwa National Park (PNP) where terrestrial lichens, wolves, bears, and moose were present. Both areas were monitored from 1974 to 2003 (30 years). The living and dead caribou on the Slates were estimated by the ‘King census’ strip transect (mean length 108±9.3 km, extremes 22-190, total 3026 km) and the Lincoln Index (mean tagged 45±3.6, extremes 15-78). The mean annual population on the Slate Islands based on the strip transects was 262±22 animals (extremes 104-606), or 7.3/km2 (29 years) and from the Lincoln Index 303±64 (extremes 181-482), or 8.4/km2 (23 years). These are the highest densities in North America and have persisted at least since 1949 (56 years). Mountain maple (Acer spicatum) interacted with caribou density creating a record in its age structure which corroborates persistence at relatively high density from c. 1930. The mean percentage of calves was 14.8±0.34% (20 years) in the fall and 14.1±1.95% (19 years) in late winter. The Slate Islands herd was regulated by the density dependent abundance of summer green foods and fall physical condition rather than density independent arboreal lichen availability and snow depths. Two wolves (1 wolf/150 caribou) crossed to the islands in 1993-94 and reduced two calf cohorts (3 and 4.9 per cent calves) while female adult survival declined from a mean of 82% to 71% and the population declined ≈100 animals. In PNP, caribou/moose/wolf populations were estimated by aerial surveys (in some years assisted by telemetry). The caribou population estimates ranged from 31 in 1979 to 9 ...